Pengaruh E-Service Quality, Perceived Ease Of Use Dan Price Terhadap Keputusan Penggunaan Jasa Transportasi Online Gojek (Studi kasus pada mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang angkatan 2020 yang menggunakan aplikasi Gojek) - Alitakupenda, Dwitaria; Mardani, Ronny Malavia; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine and analyze the influence of E-service Quality, Perceived Ease of Use and Price on Decisions to Use Gojek online transportation services. The variables used in this research are E-service Quality, Perceived Ease of Use and Price on Decisions to Use online transportation services. The research method used is multiple linear regression analysis using the SPSS (Statistical Package for Social Sciences) program. The results of this research are that E-service quality and price have a significant influence on the decision to use Gojek online transportation services. Meanwhile, perceived ease of use has no significant effect on the decision to use Gojek online transportation services. Keywords : E-Service Quality, Perceived Ease Of Use, Price, Usage Decisions.